Prevalence and characteristics of dermatitis cases in Dermatology Clinics (2020–2024): A retrospective analysis - Melati, Rima; Aryanti, Evy; Alfaqih, Muhammad Subhan; Ferianasari, Ineke Winda; Purwoko, Reza Yuridian (Science Midwifery, 2025)
Dermatitis is a common inflammatory skin condition that can significantly impact patients' quality of life. Studies on the prevalence and risk factors of dermatitis in Indonesia remain limited. To analyze the prevalence, demographic distribution, and the relationship between occupation and types of dermatitis in a dermatology clinic from 2020 to 2024. This retrospective study utilized medical record data of dermatitis patients who visited a dermatology clinic from 2020 to 2024. The variables examined included age, gender, occupation (2020–2023), case type (new/existing), and dermatitis diagnosis. Statistical analysis was conducted using the chi-square test to identify the relationship between occupation and dermatitis diagnosis. There was a significant decrease in dermatitis prevalence from 9.75% during the 2020–2023 period to 4.63% in 2024. The 25–44 year age group had the highest number of cases, with a predominance of female patients. The chi-square test showed a significant association between occupation and dermatitis diagnosis (χ² = 70.259; p < 0.05). Dermatitis remains a significant health issue with a distinct demographic distribution. Improvements in data collection and diagnosis classification are necessary for a better understanding and the development of effective prevention strategies. These findings have important implications for clinical practice and health policy in Indonesia, particularly in terms of workplace prevention and management of dermatitis.